Effects of flower age on pollination success in Lepanthes sanguinea - Guevara Ramos, Edwin (2016)
The effect of flower age on pollination has been shown to be important in promoting cross pollination when the sexual expression of flowers is age depen- dent (Ackerman 1975, Singer & Koehler 2002).